Colorectal cancer Outcomes in people with Severe Mental Illness Cohort (COSMIC): A protocol for an Australian retrospective cohort using linked administrative data - Protani, M.M.; Jordan, S.J.; Kendall, B.J.; Siskind, D.; Lawrence, David; Sara, G.; Brophy, L.; Kisely, S. (2021)
Introduction: Colorectal cancer (CRC) mortality is significantly higher in those with severe mental illness (SMI) compared with the general population, despite similar incidence rates, suggesting that barriers to optimal screening and cancer care may contribute to disparities in CRC mortality in those with SMI. This study aims to compare participation in Australia's National Bowel Cancer Screening Programme (NBCSP) in those with SMI and those in the general population. We will also investigate treatment pathways after diagnosis to determine whether treatment variations could explain differences in CRC mortality.